Analysis about the Concept of Taste's Formators. An Interpretation of Komlos' Vision - MIHAELA IOANA GURĂU (Global Economic Observer)
We see or hear around us more and more, direct or indirect, urges about what is good to consume so we ask ourselves: do we choose what and when we need something or act under the impulse of what is communicated to us through the mass media or on social media? Do we communicate something to our fellow men by mere presence, by attitude or appearance? But conversely, do we rely on what a person looks like? Does a luxurious look that makes us think of wealth bring strength to a person? Does the power of the wealth corrupts? How do we deal with corrupt manipulation through contracts with asymmetric information? Is the taste of modern human formed as a communicative manipulation of television and social media? These are some questions that I present my opinion for, as an answer to the challenge launched by Professor J Komlos in the paper "Taste’s and Consumption’s Formators". Who are the formators of taste? Do we need them? What place does communication through social media occupy in the category of taste formers? Without considering that I am exhausting the subject through this work, I invite you to reflect on it.